Histopathologic Pattern of Prostatic Lesions Observed in Autopsy Series (Journal of Dhaka Medical College, 2017)
Incidental autopsy findings may be important to study about the prevalence of prostatic lesions among the male population which remains undiagnosed. Histology is the unique method for diagnosis of silent prostatic disease. The present cross sectional study was carried out with an aim to evaluate the histopathological pattern of prostatic lesions such as nodular hyperplasia of prostate (NHP), the precancerous lesions and the latent cancer in autopsy series over the age of 40 years of male. A total number of 120 specimens of prostates were collected from the dead bodies on whom postmortem examination was done by the Department of Forensic Medicine, Dhaka Medical College and Hospital, Dhaka. All these autopsies were done for medicolegal purposes. This study confirms previous observations and concluded that nodular hyperplasia of prostate was the commonest lesion. Of the total 54 cases of NH, 27 were accompanied with transitional cell metaplasia (TCM), Squamous metaplasia, basal cell hyperplasia (BCH), low grade prostatic intraepithelial neoplasia (LGPIN), inflammation, atypical adenomatous hyperplasia (AAH), high grade prostatic intraepithelial neoplasia (HGPIN) and prostatic carcinoma (PCa). Only 27 cases were NH. Most common pattern of inflammation associated with NHP was chronic inflammation. LGPIN was present in 8 (6.6%) cases and majority were with NH. But none of the LGPIN and metaplasias were associated with carcinoma or HGPIN. The commonest age group of presentation for NH was in fifth decade and increased with advancing age. It can be concluded that many prostatic lesions can remain silent and are diagnosed only at autopsy. Considering the HGPIN and prostate cancer to be silent, the development of screening programs to detect the latent cases of the disease is recommended.J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 39-45